Characterization of guinea pig antibody responses to salivary proteins of Triatoma infestans for the development of a triatomine exposure marker. - Veronika Dorňáková; Renzo Salazar-Sanchez; Katty Borrini-Mayori; Oscar Carrion-Navarro; Michael Z Levy; Günter A Schaub; Alexandra Schwarz (Public Library of Science (PLoS), 2014)
Salivary proteins of Triatoma infestans elicit humoral immune responses in their vertebrate hosts. These immune responses indicate exposure to triatomines and thus can be a useful epidemiological tool to estimate triatomine infestation. In the present study, we analyzed antibody responses of guinea pigs to salivary antigens of different developmental stages of four T. infestans strains originating from domestic and/or peridomestic habitats in Argentina, Bolivia, Chile and Peru. We aimed to identify developmental stage- and strain-specific salivary antigens as potential markers of T. infestans exposure.In SDS-PAGE analysis of salivary proteins of T. infestans the banding pattern differed between developmental stages and strains of triatomines. Phenograms constructed from the salivary profiles separated nymphal instars, especially the 5th instar, from adults. To analyze the influence of stage- and strain-specific differences in T. infestans saliva on the antibody response of guinea pigs, twenty-one guinea pigs were exposed to 5th instar nymphs and/or adults of different T. infestans strains. Western blot analyses using sera of exposed guinea pigs revealed stage- and strain-specific variations in the humoral response of animals. In total, 27 and 17 different salivary proteins reacted with guinea pig sera using IgG and IgM antibodies, respectively. Despite all variations of recognized salivary antigens, an antigen of 35 kDa reacted with sera of almost all challenged guinea pigs.Salivary antigens are increasingly considered as an epidemiological tool to measure exposure to hematophagous arthropods, but developmental stage- and strain-specific variations in the saliva composition and the respective differences of immunogenicity are often neglected. Thus, the development of a triatomine exposure marker for surveillance studies after triatomine control campaigns requires detailed investigations. Our study resulted in the identification of a potential antigen as useful marker of T. infestans exposure.